Determinants of Green Malta Cultivation Decision and Marketing Channel Selection: Evidence from Bangladesh: Determinants of Green Malta Cultivation Decision - Hasan, Mahamudul; Faruk, Md Omor (South Asian Journal of Agriculture, 2025)
The purpose of this paper is to explore the factors that influence cultivation decision and Marketing channel choice of green Malta. In addition, determinants of farmers’ attitude and perception regarding Green Malta cultivation has been examined. A descriptive research approach has been used in the study. Data collection has been carried out from ninety (90) farmers in the districts of Pirojpur and Jhalokathi in Bangladesh. A well-structured questionnaire has been utilized and respondents were reached through in-person interviews. Descriptive statistics, logistic regression analysis, and multiple regression analysis have been employed to analyze the data. The results showed that the quantity of production has significant impact on the choice of marketing channels by the Malta farmers. The number of family members, access to loan facilities, and experience on marketing channels have significant effect on the decision to cultivate green malta. Results also showed that experience in farming and marketing channel has significant impact on attitude and perception toward green malta cultivation. South Asian J. Agric. Vol. 11, No. 2, Dec., 2025: 62-70